Optimization of permanent magnet skew in permanent magnet linear synchronous motors using finite element and statistical method (2011)
he permanent magnet skew is one of the techniques mostly used on the Permanent Magnet Linear Syn-chronous Motors (PMLSMs) to reduce the thrust ripple; even though there is a reduction in the amplitude of ripple and at the same time a significantly decrease of the motor’s thrust. This article proposes a combined technique between the Finite Elements Method (FEM) and statistical regression, to obtain an objective func-tion that will allow the achievement of the optimal Permanent Magnet (PM) skew angle, so that there is a greater reduction of ripple with the minimum thrust diminishment